ANALYSIS OF TAX COMPLIANCE AMONG MSMES IN SEMARANG: THE ROLE OF TAX LITERACY, TAX SOCIALIZATION, AND THE IMPLEMENTATION OF THE CORE TAX ADMINISTRATION SYSTEM - Sri Kawuri; Ika Listyawati; Duffin; Dewi Rafiah Pakpahan; Adi Harianto (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the effect of tax literacy, tax socialization, and the implementation of the Core Tax Administration System on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Semarang. MSMEs play a significant role in Indonesia’s economy; however, their level of tax compliance remains relatively low, creating challenges for optimizing tax revenue. Therefore, understanding the factors that influence compliance is essential. This research employs a quantitative approach using primary data collected through questionnaires distributed to MSME taxpayers in Semarang. The sampling technique used is purposive sampling, with criteria including active MSME actors who possess a Taxpayer Identification Number (NPWP). Data were analyzed using multiple linear regression to examine the relationship between independent variables tax literacy, tax socialization, and the Core Tax Administration System and the dependent variable, tax compliance. The results indicate that all three independent variables have a positive and significant effect on MSME tax compliance. The implementation of the Core Tax Administration System has the strongest influence, followed by tax literacy and tax socialization. These findings suggest that both behavioral factors (knowledge and awareness) and structural factors (system efficiency and accessibility) play important roles in shaping compliance behavior. In conclusion, improving MSME tax compliance in Semarang requires an integrated approach that enhances tax literacy, strengthens tax socialization programs, and ensures the effective implementation of digital tax systems. This study contributes to the existing literature by providing empirical evidence on the combined effects of these variables in a local context. The findings are expected to support policymakers in designing more effective tax strategies and improving overall tax administration.